Linear and integer programming - Khan, Sanaullah; Bari, Abdul; Khan, Mohammed Faisal (Cambridge Scholars Publishing, 2019)
This book is primarily intended for undergraduate and postgraduate students of statistics, mathematics, operations research, and engineering. It provides the basic concepts and methods of linear and integer linear programming. The text begins with an introduction containing the mathematical background to the subject matter, and goes on to discuss advancements the field. Formulations of various problems in diverse fields in linear and integer programming formats are also presented here. The book's presentation of the solution of various numerical problems makes the subject matter and the method.